Giertruda – Lover of Arms or Heroine of Labour? About Radical Changes in Anthroponymy - Piotr Zlotkowski (Zeszyty Cyrylo-Metodiańskie)
A reviev of: Seweryn, Agnieszka. Revolution in Anthroponymics. New Names of the Soviet Period of the First Half of the 1920s. Krakow: Avalon Press, 2021. ISBN 978-83-7730-572-0, 218 pp. [In Russian: Seweryn, Agnieszka. Революция в антропонимии: новые имена советской эпохи первой половины 20-х годов ХХ века. Kraków: Wydawnictwo Avalon, 2021.] Original title in Polish: Giertruda – miłośniczka oręża czy bohaterka pracy? Rzecz o radykalnych zmianach w antroponimii.